Radiology-Pathology Correlations of Intracranial Clots: Current Theories, Clinical Applications, and Future Directions - Benson, J.C.; Kallmes, D.F.; Larson, A.S.; Brinjikji, W. (American Journal of Neuroradiology, 2021)
SUMMARY: In recent years, there has been substantial progression in the field of stroke clot/thrombus imaging. Thrombus imaging aims to deduce the histologic composition of the clot through evaluation of various imaging characteristics. If the histology of a thrombus can be reliably determined by noninvasive imaging methods, critical information may be extrapolated about its expected response to treatment and about the patient’s clinical outcome. Crucially, as we move into an era of stroke therapy individualization, determination of the histologic composition of a clot may be able to guide precise and targeted therapeutic effort. Most radiologists, however, remain largely unfamiliar with the topic of clot imaging. This article will review the current literature regarding clot imaging, including its histologic backdrop, the correlation of images with cellular components and treatment responsiveness, and future expectations.MTmechanical thrombectomyHMCAShyperdense middle cerebral artery signNETsneutrophil extracellular trapsRBCred blood cellSVSsusceptibility vessel signTAIthrombus attenuation increase